APPLE‐Tree (Active Prevention in People at risk of dementia: Lifestyle, bEhaviour change and Technology to REducE cognitive and functional decline) programme: Protocol. (23rd December 2019) - Cooper, Claudia; Aguirre, Elisa; Barber, Julie A.; Bass, Nick; Brodaty, Henry; Burton, Alexandra; Higgs, Paul; Hunter, Rachael; Huntley, Jonathan; Lang, Iain; Kales, Helen C.; Marchant, Natalie L.; et al.
Abstract : Background: Observational studies indicate that approximately a third of dementia cases are attributable to modifiable cardiometabolic, physical and mental health, and social and lifestyle risk factors. There is evidence that intensive behaviour change interventions targeting these factors can reduce cognitive decline. Methods and analysis: We will design and test a low intensity, secondary dementia‐prevention programme (Active Prevention in People at risk of dementia: Lifestyle, bEhaviour change and Technology to REducE cognitive and functional decline, "APPLE‐Tree") to slow cognitive decline in people with subjective cognitive decline with or without objective cognitive impairment. We will embed our work within social science research to understand how dementia prevention is currently delivered and structured. We will carry out systematic reviews and around 50 qualitative interviews with stakeholders, using findings to coproduce the APPLE‐Tree intervention. We plan a 10‐session group intervention, involving personalised goal‐setting, with individual sessions for those unable or unwilling to attend groups, delivered by psychology assistants who will be trained and supervised by clinical psychologists. The coproduction group (including public and patient involvement [PPI], academic and clinical/third‐sector professional representatives) will use the Behaviour Change Wheel theoretical framework to develop it. We will recruit and randomly allocate 704 participants, 1:1 to the intervention: informational control group. This sample size is sufficient to detect a between‐group difference at 2 years of 0.15 on the primary outcome (cognition: modified neuropsychological test battery; 90% power, 5% significance, effect size 0.25, SD 0.6). Dissemination: We will work with Public Health England and third‐sector partners to produce an effective national implementation approach, so that if our intervention works, it is used in practice.